PENGARUH MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA KELAS IV DI SDN KELURAHAN RAWAMANGUN - Dilla Nurul Aulia; Dudung Amir Soleh; Engga Dallion (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Mathematical connection ability is a fundamental competency in mathematics learning that allows students to relate mathematical concepts to one another and to real-life situations. However, this ability remains low among Indonesian elementary school students, as evidenced by the 2022 PISA results in which nearly 0% of Indonesian students reached proficiency at the mathematical connection level (Level 5–6). Preliminary observations at State Elementary Schools in Rawamangun Subdistrict also revealed that instruction was predominantly conventional, with student worksheets that did not support the development of mathematical connection ability. This quasi-experimental study employed a pretest-posttest two-group control design to examine the effect of the Missouri Mathematics Project (MMP) learning model on the mathematical connection ability of fourth-grade students, reinforced by contextual visual-manipulative student worksheets (LKPD). A total of 63 students participated: 31 in the experimental class (MMP model) and 32 in the control class (Expository model). Data collection was carried out through a structured essay test of 10 items validated theoretically and empirically. The Independent Sample T-Test showed a significance value of 0.001 (< 0.05), with the experimental class mean post-test score (31.58) exceeding the control class (25.56). The N-Gain score of the experimental class (68.55%) was higher than the control class (49.97%). These results indicate that the MMP model positively and significantly influences the mathematical connection ability of fourth-grade elementary school students.